Anesthetic Management for Cesarean Delivery in a Patient with a Gigantic Intracranial Tumor. (11th April 2020) - dos Santos e Santos, C.; Mason, C. L.; Neill, J. S.; Grayson, B. E.; Calimaran, A.; Bacon, D. R.
Abstract : A 31-year-old G5P1 patient with unremarkable past medical history at 29 weeks of gestation was diagnosed with a gigantic left frontotemporal brain mass. Initial clinical management as an inpatient achieved an improvement in the symptoms. The patient and surgical team agreed to schedule a cesarean delivery at 32 weeks of gestation if no neurological deterioration was observed. Intraoperative course with general endotracheal anesthesia and bilateral transversus abdominis plane block was uneventful and promoted efficient postoperative pain control. Seven days after delivery, the patient underwent craniotomy for brain tumor resection. This report describes the anesthetic management of a patient with an intracranial tumor during pregnancy.